Level of insight and clinical features of obsessive-compulsive disorder with and without body dysmorphic disorder - Nakata, Ana Cristina Gargano; Diniz, Juliana B.; Torres, Albina Rodrigues [UNESP]; De Mathis, Maria Alice; Fossaluza, Victor; Braganças, Carlos Alberto; Ferrão, Ygor; Miguel, Euripedes C. (My University, 2007)
Introduction: Body dysmorphic disorder (BDD) and obsessive-compulsive disorder (OCD) have several similarities and are included among the obsessive-compulsive spectrum of disorders. However, the content of preoccupations and level of insight of BDD patients differ from OCD patients. Objective: To compare the level of insight regarding obsessive-compulsive symptoms (OCS) and other clinical features in OCD patients with and without comorbid BDD. Methods: We evaluated 103 OCD patients (n=25, comorbid BDD), according to Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria using the Structured Clinical Interview for DSM-IV, the Yale-Brown Obsessive-Compulsive Scale, the University of Sao Paulo Sensory Phenomena Scale, the Beck Depression and Anxiety Inventories, and the Brown Assessment of Beliefs Scale. Resylts: The study groups differed significantly on several clinical features, including level of insight. A worse level of insight regarding OCS was independently associated with the presence of comorbid BDD. Lower educational level, more psychiatric comorbidities, presence of somatic and hoarding obsessions, and presence of intrusive images were associated with BDD comorbidity, even after adjusting for possible confounders. Conclusion: The presence of BDD in OCD patients is associated with poorer insight into obsessional beliefs and higher morbidity, reflected by lower educational levels and higher number of psychiatric comorbid disorders in general.
Keywords: adolescent; adult; Beck Anxiety Inventory; Beck Depression Inventory; body dysmorphic disorder; child; clinical feature; comorbidity; comparative study; confounding variable; controlled study; diagnostic and statistical manual of mental disorders; education; human; introspection; major clinical study; morbidity; obsessive compulsive disorder; priority journal; psychiatry; rating scale; statistical significance; structured interview; symptom; Adolescent; Adult; Awareness; Brazil; Comorbidity; Culture; Diagnosis, Differential; Diagnostic and Statistical Manual of Mental Disorders; Female; Humans; Male; Mental Disorders; Middle Aged; Obsessive-Compulsive Disorder; Somatoform Disorders